A genetic memory initiates the epigenetic loop necessary to preserve centromere position. (18th September 2020) - Hoffmann, Sebastian; Izquierdo, Helena M; Gamba, Riccardo; Chardon, Florian; Dumont, Marie; Keizer, Veer; Hervé, Solène; McNulty, Shannon M; Sullivan, Beth A; Manel, Nicolas; Fachinetti, Daniele
Abstract: Centromeres are built on repetitive DNA sequences (CenDNA) and a specific chromatin enriched with the histone H3 variant CENP‐A, the epigenetic mark that identifies centromere position. Here, we interrogate the importance of CenDNA in centromere specification by developing a system to rapidly remove and reactivate CENP‐A (CENP‐A OFF/ON ). Using this system, we define the temporal cascade of events necessary to maintain centromere position. We unveil that CENP‐B bound to CenDNA provides memory for maintenance on human centromeres by promoting de novo CENP‐A deposition. Indeed, lack of CENP‐B favors neocentromere formation under selective pressure. Occasionally, CENP‐B triggers centromere re‐activation initiated by CENP‐C, but not CENP‐A, recruitment at both ectopic and native centromeres. This is then sufficient to initiate the CENP‐A‐based epigenetic loop. Finally, we identify a population of CENP‐A‐negative, CENP‐B/C‐positive resting CD4 + T cells capable to re‐express and reassembles CENP‐A upon cell cycle entry, demonstrating the physiological importance of the genetic memory. Synopsis: Despite centromere position being epigenetically defined, all human centromeres are built on long stretches of repetitive DNA. This work defines a genetic feature in human cells that provides memory for maintenance of native human centromeres, but is also capable of occasionally initiating epigenetic definition of centromeres. Preexisting CENP‐A nucleosomes are not required to avert sliding of centromere position, or to define a specific number of CENP‐A molecules. CENP‐B bound to centromeric DNA provides memory for maintenance of human centromeres, to prevent movement of centromere position. CENP‐C, but not CENP‐A, is the initiation factor for de novo centromere formation via its recruitment to CENP‐B-bound centromeric DNA. A subpopulation of resting T lymphocytes lacks CENP‐A, but is capable of re‐assembling it upon activation and cell cycle entry. Abstract : Rapid removal and reactivation of CENP‐A defines the temporal cascade of events necessary to maintain centromere position, with DNA‐bound CENP‐B providing memory and preventing movement of centromere position.